Kajian Kajian In Silico Aktivitas Ekstrak Daun Mangga (Mangifera indica L.) Sebagai Antidiabetes Tipe 2 - Janatun Na’imah; Anindi Lupita Nasyanka; Diah Ratnasari (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Type 2 diabetes mellitus is the most common type of diabetes in the world. Type 2 diabetes mellitus is caused by an increase in blood sugar due to a decrease in low insulin secretion by the pancreas gland. Pharmacological therapy for type 2 diabetes, namely oral antidiabetic drugs (OAD) or insulin such as acarbose, metformin, or voglibose has been reported to have side effects. Side effects that occur, such as gastrointestinal disturbances (diarrhea and flatulence), liver disorders, dizziness, nausea and vomiting. Thus, herbal ingredients are an alternative in the treatment of diabetes mellitus. In this study, mango leaf extract, namely mangiferin, was suspected as an antidiabetic compound. The purpose of this study was to determine the interaction of mangiferin which is an extract of mango leaves (Mangifera Indica L.) with -glucosidase in silico. The results showed that mangiferin as a type 2 antidiabetic compound by producing an G value between -glucosidase and mangiferin of -38.89 kcal/mol. The interaction that occurs is hydrogen bonding between mangiferin and amino acid residues Glu553, Asn551, Arg500 and Tyr460, Phe461. Keywords: α-glucosidase, in silico, mangiferin, mango leaf,